Topical moistening of mastectomy wounds with diluted tranexamic acid to reduce bleeding: randomized clinical trial. Issue 2 (26th December 2019) - Ausen, K.; Hagen, A. I.; Østbyhaug, H. S.; Olafsson, S.; Kvalsund, B. J.; Spigset, O.; Pleym, H.
Abstract : Background: Topical administration of tranexamic acid (TXA) may be an alternative to intravenous administration to reduce bleeding with a lower risk of systemic adverse events. The aim of this study was to investigate whether moistening a surgical wound with TXA before closure, leaving a thin film of drug only, would reduce postoperative bleeding. Methods: This was a two‐centre, stratified, parallel‐group, placebo‐controlled, double‐blind RCT. Patients undergoing mastectomy with or without axillary lymph node clearance were randomized 1 : 1 to moistening of wound surface before closure with either 25 mg/ml TXA or 0·9 per cent sodium chloride (placebo). The primary endpoint was postoperative bleeding as measured by drain production in the first 24 h. Secondary endpoints were early haematoma, total drain production, postoperative complications and late aspirations of seroma within 3 months. Results: Between 1 January 2016 and 31 August 2018, 208 patients were randomized. Two patients were converted to a different surgical procedure at surgery, and four did not receive the intervention owing to technical error. Thus, 202 patients were included in the study (101 in the TXA and 101 in the placebo group). TXA reduced mean drain production at 24 h (110 versus 144 ml; mean difference 34 (95 per cent c.i. 8 to 60) ml, P = 0·011). One patient in the TXA group had early haematoma compared with seven in the placebo group (odds ratio (OR) 0·13 (95 per cent c.i. 0·02 to 1·07); P = 0·057). There was no significant difference in postoperative complications between TXA and placebo (13 versus 10; OR 1·11 (0·45 to 2·73), P = 0·824) or need for late seroma aspirations (79 versus 67 per cent; OR 1·83 (0·91 to 3·68), P = 0·089). Conclusion: Moistening the wound with TXA 25 mg/ml before closure reduces postoperative bleeding within the first 24 h in patients undergoing mastectomy. Registration number: NCT02627560 (https://clinicaltrials.gov ). Abstract : Moistening surgical wounds with tranexamic acid 25 mg/ml before closure is a simple, low‐cost intervention that reduces bleeding by one‐third and may reduce risk of rebleeding. The effect is comparable to intravenous administration, with a reduced risk of systemic adverse events. The authors propose this preventive measure for general reduction of postoperative bleeding. Local tranexamic acid reduces bleeding after mastectomy Abstract : Antecedentes: La administración tópica de ácido tranexámico ( tranexamic acid, TXA) puede ser una alternativa a la administración por vía intravenosa para reducir la hemorragia, con menor riesgo de eventos sistémicos adversos. El objetivo de este estudio fue investigar si humedecer la herida quirúrgica con TXA 25 mg/ml antes del cierre de la incisión dejando solo una fina película de fármaco, reducía la hemorragia postoperatoria. Métodos: Se trata de un ensayo clínico aleatorizado, a doble ciego, controlado con placebo, de grupos paralelos, estratificado por dos centros. Las pacientes sometidas a mastectomía con/sin resección de los ganglios linfáticos axilares se asignaron al azar 1:1 para la humidificación de la superficie de la herida antes del cierre con TXA 25 mg/ml o con NaCl al 0, 9% (placebo). El objetivo primario fue la hemorragia postoperatoria medida por el débito del drenaje durante las primeras 24 horas. Los objetivos secundarios fueron el desarrollo de hematoma precoz, el débito total del drenaje, las complicaciones postoperatorias y la necesidad de aspiración de un seroma tardío durante los primeros 3 meses tras la cirugía. Resultados: Entre el 1 de enero de 2016 y el 31 de agosto de 2018, 208 pacientes fueron asignadas al azar. En dos pacientes tuvo que realizarse un procedimiento quirúrgico diferente durante el periodo perioperatorio y cuatro pacientes no recibieron la intervención por errores técnicos. Por lo tanto, se incluyeron 202 pacientes en el estudio (101 fueron tratadas con TXA y 101 con placebo). El TXA redujo el débito medio del drenaje a las 24 horas (110 versus 144 ml, diferencia media 34 ml, i.c. del 95%: 8 a 60 ml, P = 0, 010). Se presentó un hematoma precoz en una paciente del grupo del TXA versus siete pacientes tratadas con placebo (razón de oportunidades, odds ratio, OR 0, 13, i.c. del 95% 0, 02‐1, 07, P = 0, 057). No hubo diferencias significativas en las complicaciones postoperatorias entre TXA y placebo (13 versus 10, OR 1, 11, i.c. del 95% 0, 45‐2, 73, P = 0, 824) o la necesidad de aspiración tardía de seromas (79, 3 versus 66, 6%, OR 1, 83, i.c. del 95% 0, 91‐3, 68, P = 0, 089). Conclusión: Humedecer la herida antes del cierre con TXA 25 mg/ml reduce la hemorragia postoperatoria durante las primeras 24 horas en pacientes sometidas a mastectomía.